Physical variables - lake temperature profile from Erken, ice-free anchored TW-profile - Erken Laboratory (Uppsala University, 2020)
High frequency temperature profiles are measured in lakes of SITES Water to be able to determine the thermal structure.
Erken Laboratory (2020). Physical variables - lake temperature profile from Erken, ice-free anchored TW-profile, 2014-04-04–2014-11-03 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/1SIdT3Qv1Q61xp2ZbBnn94c8
Keywords: Erken Laboratory; Time instant; Time instant; Water temperature; Water temperature; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap